A hint baroque: the massive spectacle as representation politics - Ángel-Reyes, Johanna (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
These lines are written with the aim of establishing bases for a critical analysis of state cultural policies in Mexico and Latin America, which favor the taking root of festive shows in spaces denoted as public, where the mechanisms of representation derive from an update of the same baroque instruments of domination that prevail from the ideological forging of the colonies. Attention is drawn to the definition of citizenship that clearly appeals to symbolic actions, which involve linking culture as a cultural capital, and redefining public space as a virtual space for representation.